Canada, train car on siding near Hudson Bay warehouse in Moosonee - Platt, Robert S. (Robert Swanton), 1891-1964 (1934)
Due to a malfunction inside Platt's camera, the majority of his first 8,000 images, dating from 1919 to 1933, have blurred areas where the unexposed film was not laying flat inside the camera. His 35mm photography after 1933 does not show this defect, but the condition of the film is rather poor, having been housed between loose sheets of paper in cardboard boxes for over 50 years. The majority of images he took from 1933-1963 are severely scratched. Therefore, only a small portion of Platt's photography has been chosen for online presentation. 8/12 Moosonee. Car on siding, HB [Hudson's Bay] warehouse. NE Grayscale Platt Nitrate Negative, Box 216 of 250